Having trouble with a prove, I'm not sure where to put this question.
Follow Math Help Forum on Facebook and Google+
y = b/2x Substitute it in the first equation and simplify. Then solve the quadratics to get x^2.
Originally Posted by sa-ri-ga-ma y = b/2x Substitute it in the first equation and simplify. Then solve the quadratics to get x^2. hi, thanks. I got that part, I'm just not sure how to simplify it.
x^2 - (b / (2x))^2 - a = 0 4x^4 - 4ax^2 - b^2 = 0 Let u = x^2 4u^2 - 4au - b^2 = 0 Can you finish it?
Originally Posted by Wilmer x^2 - (b / (2x))^2 - a = 0 4x^4 - 4ax^2 - b^2 = 0 Let u = x^2 4u^2 - 4au - b^2 = 0 Can you finish it? thanks, I think I still am having a bit of trouble with it. Do I have to complete the square or?
Originally Posted by chessweicong thanks, I think I still am having a bit of trouble with it. Do I have to complete the square or? or use the quadratic formula.
Originally Posted by a tutor or use the quadratic formula. ah, ok. thank you very much
View Tag Cloud